Severe malnutrition in children in Papua New Guinea: effect of a multi-faceted intervention to improve quality of care and nutritional outcomes. (2nd January 2017) - Landi, Michael; Swakin, Evelyn; Minijihau, Cecilia; Welch, Henry; Tefuarani, Nakapi; Duke, Trevor
Abstract : Background and aims: Severe malnutrition remains a major problem in Papua New Guinea; it is associated with 11% of paediatric hospital admissions and 33% of all child deaths, with a case fatality rate around 20%. This article aims to evaluate the effectiveness of a multi-faceted intervention for improving care for children with severe malnutrition. Methods: Severe malnutrition was defined as weight-for-age (WFA) <-3 Z-scores with severe wasting or mid upper arm circumference <115 mm or generalised oedema owing to malnutrition. The intervention included training for health-care workers on WHO guidelines for severe malnutrition, ward-round checklists, posters and support for nurses to provide better patient nutrition. Three point prevalence surveys were conducted; one before the intervention and two afterwards at 3-month intervals. The main outcomes were weight change since admission, energy intake and the proportion of the calculated required energy intake in the previous 24 hours. Each stage of the WHO guidelines for severe malnutrition management was assessed for adherence. Results: There were significant improvements in the WHO steps for the management of severe malnutrition. At pre-intervention baseline, children received a median of 356 ml/day (IQR 178–450): 31% (95% CI 21–48) of their estimated daily energy requirements for weight. In the first follow-up survey, children received a median of 820 (IQR 600–1110) ml/day: 98% (95% CI 67–100) of daily energy requirements; and in the second follow-up survey they received 780 (IQR 480–900) ml/day: 86% (95% CI 46–100%) of daily requirement ( P< 0.001 both for volume received and percentage of energy requirements). Median weight gain prior to the intervention was 1.55 g/kg/day (IQR -4.3–6.0) which increased to 5.56 g/kg/day (IQR -3.7–12.0) and 10.19 g/kg/day (IQR 0–16.0) in the first and second follow-up surveys, respectively ( P =0.013). Conclusion: Implementation of a multi-faceted intervention to improve the management of children with severe malnutrition was associated with improved quality of care and improved weight gain.